(untitled) (Communicare: Journal for Communication Studies in Africa, 2022)
The purpose of the study was to develop a hybrid quantitative audit of organisational communicationsatisfaction for the public service. In Study One, a two-factor solution was obtained, based onparallel analysis as a factor determination strategy with data obtained from 264 civil servantsusing a 30 item measure. In Study Two, the items of the new EFA-generated organisationalcommunication satisfaction scale were renumbered consecutively and the scale was crossvalidatedon a new sample of 288 civil servants from the Addis Ababa City Administration. Thecross-validation necessitated model respecification and re-estimation. The respecified modelunderwent validation at different levels. All seven aspects of validity, namely content validity,construct validity, factorial validity, reliability, convergent validity, discriminant validity andnomological validity were addressed and found to be adequate, pointing to a refinement in themeasurement of communication satisfaction. However, limitations are also indicated as avenuesfor further enquiry.